Імпортозаміщення як стратегічний чинник підвищення ефективності виробничих, логістичних та інноваційних процесів підприємства - Шуміло, Ольга Станіславівна; Коптєва (Фадєєва), Ганна Миколаївна; Шелест, Олексій Леонідович (Український державний університет науки і технологій, 2025)
У статті обґрунтовано та доповнено теоретичні і практичні засади імпортозаміщення. У результаті проведеного компаративного аналізу досліджено суть поняття «імпортозаміщення» й виділені особливості визначень науковців. Узагальнюючи існуючі дослідження науковців доповнено теоретичний базис імпортозаміщення авторським визначенням. Розглянуто основні групи стратегій імпортозаміщення, що існують у світовій практиці з належними їм характеристиками, інструментами досягнення очікуваних результатів. Зазначено про необхідність формування стратегії імпортозаміщення на рівні держави та підприємства. Визначено цілі політики імпортозаміщення на державному рівні та на рівні діяльності підприємства. Досліджено вплив імпорто-заміщення як стратегічного чинника на виробничу, логістичну, та інноваційну діяльність підприємства, визначено ефект від впливу. Зазначено про важливість та переваги імпортозаміщення для держави та підприємства.

The article examines the theoretical and practical foundations of import substitution. As a result of a comparative analysis, the essence of the concept of “import substitution” is examined and the peculiarities of scientists' definitions are highlighted. Summarizing existing scientific research, the theoretical basis of import substitution is supplemented with the author's definition. Import substitution is proposed to be understood as a process, as a strategy of an enterprise based on the principles of efficiency and economic feasibility of import substitution within the framework of a comprehensive state policy and aimed at improving the efficiency of production, logistics, and innovation processes at the enterprise. The article considers the historical aspects of import substitution. The main groups of import substitution strategies that exist in global practice are described, along with their characteristics and the tools for achieving the expected results. Among them, the following groups are highlighted: strategy for relatively underdeveloped domestic industries; development and creation of new domestic industries; stimulation of new promising domestic industries that will increase the volume of products for the domestic market and for export in the future. It is noted that import substitution by industry can be classified into three categories: substitution of imported resources, especially energy resources; substitution of consumer goods; substitution of goods intended for production. The main groups of import substitution strategies that exist in global practice are described, along with their characteristics and the tools for achieving the expected results. Among them, the following groups are highlighted: strategy for relatively underdeveloped domestic industries; development and creation of new domestic industries; stimulation of new promising domestic industries that will increase the volume of products for the domestic market and for export in the future. It is noted that import substitution by industry can be classified into three categories: substitution of imported resources, especially energy; substitution of consumer goods; substitution of goods intended for production.
Import substitution as a strategic factor in improving the efficiency of production, logistics, and innovation processes in enterprises
Keywords: імпортозаміщення; ефективність; підприємство; виробництво; логістика; інновації; import substitution; efficiency; enterprise; production; logistics; innovation